The Machine-Gunners - Westall, Robert (Macmillan Publishers Ltd, 1975)
Some bright kid's got a gun and 2000 rounds of live ammo. And that gun's no peashooter. It'll go through a brick wall at a quarter of a mile.' Chas McGill has the second-best collection of war souvenirs in Garmouth, and he desperately wants it to be the best. When he stumbles across the remains of a German bomber crashed in the woods - its shiny, black machine-gun still intact - he grabs his chance. Soon he's masterminding his own war effort with dangerous and unexpected results....
Keywords: Fiction; General, Classic